Flexible robotic endoscopy systems and the future ahead - Seah, Timothy Tian En (Humana Press, Cham, 2020)
Robotics enables a variety of unconventional actuation strategies to be used for endoscopes, resulting in reduced trauma to the GI tract. For transmission of force to distally mounted endoscopic instruments, robotically actuated tendon-sheath mechanisms are the current state of the art. Robotics in surgical endoscopy enables an ergonomic mapping of the surgeon movements to remotely control the slave arms as well as to facilitate tissue manipulation. The learning curve for difficult procedures such as endoscopic submucosal dissection and full-thickness resection can be significantly reduced. Improved surgical outcomes are also observed from clinical and preclinical trials. The technology behind master-slave surgical robotics will continue to mature, with the addition of position and force sensors enabling better control and tactile feedback. More robotic-assisted gastrointestinal (GI) luminal and natural orifice transluminal endoscopic surgery (NOTES) systems are expected to be conducted in future, and gastroenterologists will have a key collaborative role to play.